Comparación de métodos para la determinación de edad en el vampiro común Desmodus rotundus (Chiroptera: Phyllostomidae) - Núñez, Alejandro (1997)
Age estimation methods in the common vampire bat (Desmodus rotundus ) were compared on 81 individuals from a natural cave in Ampascachi, Salta province (Argentina). Age was assessed by counting incisor growth lines in the root cementum. This estimation was compared with forearm and tibia lenght and dentinecementum and percentage of dentine attrition índices. Age estimation by both forearm and tibia lenght were less reliable (Pe8ISon r = 0.29 and 0.33 respectively) than dentine attrition and dentine-cementum indices (r = -0.90 and 0.88 respectively). McNemarand Cohen-Kappa tests showed that dentine attrition index had the best fit with aging by growth lines